Bothrops leucurus venom induces acute hypotension in rats by means of its phospholipase A2 (blD-PLA2). (15th October 2020) - Menezes, Thiago N.; Naumann, Gustavo B.; Peixoto, Pollyana; Rouver, Wender N.; Gomes, Helena L.; Campos, Fabiana V.; Borges, Marcia H.; dos Santos, Roger L.; Bissoli, Nazaré S.; Sanchez, Eladio F.; Figueiredo, Suely G.
Abstract: Cardiovascular effects induced by snake venoms, in spite of having a crucial role in the outcome of the envenomation, have been less studied than other toxic activities displayed by these venoms. In this study we evaluated acute cardiovascular responses to Bothrops leucurus venom - Bl-V - both in vivo, in anesthetized rats, and in vitro, in isolated rat mesenteric resistance arteries. Bl-V (10–100 μg protein/kg) caused dose-dependent hypotension, followed by gradual recovery (2–20 min) to basal levels, and induced dose-dependent (1–20 μg/mL) vasodilation in pre-contracted arteries, what was more pronounced when the endothelium remained intact. These effects were partially counteracted by pre-treatment with indomethacin (cyclooxygenase inhibitor). Prior incubation of Bl-V with commercial pentavalent Bothrops antivenom also attenuated the cardiovascular effects induced by the venom, in spite of it not being among the venoms used for the development of the bothropic antivenom. Through an approach based on two chromatographic steps and mass spectrometry (MALDI-ToF and MALDI-ISD), a component with acute cardiovascular effects was isolated and identified as the basic phospholipase bl D-PLA2, previously purified from the venom of B. leucurus . Taken together, our results show that, at low doses, the venom of B. leucurus induces transient, acute hypotension in anesthetized rats following systemic vasodilation in a dose-dependent way. In addition, we provide clear evidence of the involvement of the enzymatic activity of bl D-PLA2 in this cardiovascular response, acting via the production of vasodilating prostanoids. Highlights: Bothrops leucurus venom (Bl-V) induces a sudden, transient dose-dependent hypotension. Bl-V promotes dose-dependent vasodilation in pre-contracted mesenteric arteries. The cardiovascular responses induced by Bl-V are partially counteracted by indomethacin. The cardiovascular responses induced by Bl-V are attenuated by pre-incubation with pentavalent Bothrops antivenom. The basic phospholipase bl D-PLA2 is responsible for the cardiovascular effects induced by the venom.